1992
DOI: 10.1159/000247612
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Onychomycosis with Amorolfine 5% Nail Lacquer: Comparative Efficacy and Tolerability of Once and Twice Weekly Use

Abstract: 456 patients with onychomycosis were treated once or twice weekly for up to 6 months with amorolfine 5% nail lacquer in an open, randomized study. The patients were examined at monthly intervals during treatment and followed-up 1 and 3 months after completion of treatment. Slightly better cure rates were achieved with twice weekly use than with once weekly use (overall cure rates 54.2 vs. 46.0% p = 0.4). An overall cure or improvement was achieved in 74 and 68% of patients receiving twice- and once-weekly trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
2
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 3 publications
1
21
2
2
Order By: Relevance
“…Most studies with nail lacquers are >15 years old or did not assess complete cure at 1 year which is the gold standard for onychomycosis treatment evaluation [20] . There is some new evidence regarding the efficacy of nail lacquers when used alone for the treatment of onychomycosis [7] .…”
mentioning
confidence: 99%
“…Most studies with nail lacquers are >15 years old or did not assess complete cure at 1 year which is the gold standard for onychomycosis treatment evaluation [20] . There is some new evidence regarding the efficacy of nail lacquers when used alone for the treatment of onychomycosis [7] .…”
mentioning
confidence: 99%
“…For example, the 28% formulation of tioconazole was reported to have a cure rate of only 20 to 22% (19). A multicenter study of 456 patients demonstrated a 54% clinical response rate for amorolfine nail lacquer; however, patients in this study had no nail bed involvement (27). Ciclopirox, the only FDA-approved topical agent for the treatment of onychomycosis in the United States, achieves drug concentrations in the nail considerably higher than the MIC of ciclopirox for dermatophytes (5).…”
mentioning
confidence: 66%
“…In those cases, combination therapy has been found to be promising in ameliorating the overall cure rate of onychomycosis [52][53][54][55]. The use of combination approach and the application of antifungal drug synergy is a wellknown concept in mycology.…”
Section: Combination Therapymentioning
confidence: 99%
“…The use of combination approach and the application of antifungal drug synergy is a wellknown concept in mycology. The combination of two or more drugs can result in augmented efficacy, rapidity of effects, a broader spectrum of activity and improved patient tolerability [55][56][57][58][59]. The benefits of combination therapy were first shown with griseofulvin as the standard therapy for the treatment of onychomycosis (due to dermatophytes) for the last 30 years.…”
Section: Combination Therapymentioning
confidence: 99%